Proving Surface Plasmons in Graphene Nanoribbons Organized as 2D Periodic Arrays and Potential Applications in Biosensors - Talia Tene; Marco Guevara; Jiří Svozilík; Diana Coello-Fiallos; Jorge Briceño; Cristian Vacacela Gomez (Chemosensors, 2022)
Surface-plasmon-based biosensors have become excellent platforms for detecting biomolecular interactions. While there are several methods to exciting surface plasmons, the major challenge is improving their sensitivity. In relation to this, graphene-based nanomaterials have been theoretically and experimentally proven to increase the sensitivity of surface plasmons. Notably, graphene nanoribbons display more versatile electronic and optical properties due to their controllable bandgaps in comparison to those of zero-gap graphene. In this work, we use a semi-analytical approach to investigate the plasmonic character of two-dimensional graphene nanoribbon arrays, considering free-standing models, i.e., models in which contact with the supporting substrate does not affect their electronic properties. Our findings provide evidence that the plasmon frequency and plasmon dispersion are highly sensitive to geometrical factors or the experimental setup within the terahertz regime. More importantly, possible applications in the molecular detection of lactose, α-thrombin, chlorpyrifos-methyl, glucose, and malaria are discussed. These predictions can be used in future experiments, which, according to what is reported here, can be correctly fitted to the input parameters of possible biosensors based on graphene nanoribbon arrays.